1972
DOI: 10.5935/0305-7518.19720025
|View full text |Cite
|
Sign up to set email alerts
|

Arthropod Feed ing Experiments in Lepromatous Leprosy

Abstract: Laboratory-reared Culex fa tigans and Cimex hemipterus were fed on untreated lepromatous leprosy patients. The presence of acid-fast bacteria in a high proportion of these insects after feeding showed that they can take up the bacilli from the patients' blood. The dependence of infestation of fed insects on the degree of bacteraemia in patients and the detection in Cimex of bacteria-laden leucocytes suggest that the insects took up the bacilli along with the blood rather than fr om the skin. Results of mouse f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…The role of Cimex lectularius as a vector for blood‐borne pathogen transmission continues to be investigated. Controlled scientific studies have demonstrated in vivo incubation of organisms carrying approximately 20 different human illnesses, including leishmaniasis, American trypanosomiasis, rickettsia, pasturella, tularemia, yersina, Q fever, plaque, relapsing fever, leprosy, oriental sore, and brucellosis (10,49–53). To date, no substantial evidence of transmission of these organisms from bedbugs to humans has been recorded (4,15,54).…”
Section: Discussionmentioning
confidence: 99%
“…The role of Cimex lectularius as a vector for blood‐borne pathogen transmission continues to be investigated. Controlled scientific studies have demonstrated in vivo incubation of organisms carrying approximately 20 different human illnesses, including leishmaniasis, American trypanosomiasis, rickettsia, pasturella, tularemia, yersina, Q fever, plaque, relapsing fever, leprosy, oriental sore, and brucellosis (10,49–53). To date, no substantial evidence of transmission of these organisms from bedbugs to humans has been recorded (4,15,54).…”
Section: Discussionmentioning
confidence: 99%
“…[122][123][124] In several studies, leprosy patients were used to test the uptake of leprosy bacilli from lesions. [125][126][127][128][129][130][131] In others, leprous material from patients was used to feed insects. [132][133][134] Insects were also collected from leprosy patient's homes.…”
Section: Potential Vectors (Seementioning
confidence: 99%
“…In fact, there are several biting arthropods residing in highly endemic areas of leprosy that theoretically might act as a vector of M. leprae [ 55 – 66 ]. In some studies, the distribution of single lesions of tuberculoid leprosy correlated with exposed skin areas [ 60 , 61 ]. Mechanical studies have demonstrated the feasibility of biting arthropods to uptake M. leprae since large numbers of bacilli are readily available within cutaneous lesions to the biting apparatus of many species of arthropods among individuals with untreated multibacillary leprosy [ 59 , 61 – 66 ].…”
Section: Arthropods As Vectors Of M Leprae Transmmentioning
confidence: 99%
“…In some studies, the distribution of single lesions of tuberculoid leprosy correlated with exposed skin areas [ 60 , 61 ]. Mechanical studies have demonstrated the feasibility of biting arthropods to uptake M. leprae since large numbers of bacilli are readily available within cutaneous lesions to the biting apparatus of many species of arthropods among individuals with untreated multibacillary leprosy [ 59 , 61 – 66 ]. Additionally, it has been shown that patients with lepromatous leprosy by developing bacteremia may make viable bacilli available to biting arthropods [ 63 65 ].…”
Section: Arthropods As Vectors Of M Leprae Transmmentioning
confidence: 99%